2017
DOI: 10.1155/2017/9365814
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Initial Moisture Content on Heat and Moisture Transfer in Firefighters’ Protective Clothing

Abstract: This paper presents a model for heat and moisture transfer through firefighters' protective clothing (FPC) during radiation exposure. The model, which accounts for air gaps in the FPC as well as heat transfer through human skin, investigates the effect of different initial moisture contents on the thermal insulation performance of FPC. Temperature, water vapor density, and the volume fraction of liquid water profiles were monitored during the simulation, and the heat quantity absorbed by water evaporation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The authors concluded that while moisture decreases the heat flux towards the skin, it increases thermal hazard due to higher stored energy in the garment. Huang et al [15] J o u r n a l P r e -p r o o f numerically studied the relative humidity (0-90 % R.H) effect on the thermal performance of a 3 layer protective firefighting jacket exposure to a flux of 5 kW/m 2 . They found a positive trend between relative humidity and second-degree burn time.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that while moisture decreases the heat flux towards the skin, it increases thermal hazard due to higher stored energy in the garment. Huang et al [15] J o u r n a l P r e -p r o o f numerically studied the relative humidity (0-90 % R.H) effect on the thermal performance of a 3 layer protective firefighting jacket exposure to a flux of 5 kW/m 2 . They found a positive trend between relative humidity and second-degree burn time.…”
Section: Introductionmentioning
confidence: 99%